A review of the relationship between gut microbiota and osteoporosis in high altitude environments - Yajun Qiao; Huimin Zheng; Ruiying Cheng; Lin Rong; Juan Guo; Guoqiang Li; Lixin Wei; Tingting Gao; Zhongshu Shan; Hongtao Bi (Journal of Health, Population and Nutrition)
Abstract Osteoporosis is the most common bone metabolic disease, but the altitude environment increases the incidence of osteoporosis. Gut microbiota is a key potential target for osteoporosis. However, it is not clear how plateau environment (hypoxia/hypothermia) interferes with the development of osteoporosis by affecting gut microbiota. Therefore, the aim of this paper is to explain that hypoxia and hypothermia environment is involved in bone metabolism regulation by affecting gut microbiota, which may be one of the pathways for the early development of osteoporosis. This paper reviews a large number of clinical and basic studies to systematically evaluate the pathway by which gut microbiota is involved in regulating bone metabolism, and further discuss the potential effects of hypoxia/hypothermia on gut microbiota in regulating bone metabolism. This review summarizes that gut microbiota was mainly involved in the regulation of bone metabolism through immune, hormone and metabolite levels, while hypothermia/hypoxia affected bone metabolism mainly through the effects of microbial immune response and short-chain fatty acids (SCFAs) secretion. In addition, our interpretation of Tibetan dietary patterns reveals a new potential complementary therapy for osteoporosis intervention. Although the initial results are exciting, more trials are needed to understand the interactions between diet, gut microbiota, and bone metabolism.